APPLICATION OF VIRTUAL REALITY TECHNOLOGY IN AGRICULTURAL TRAINING IN SWITZERLAND - Hnin Thiri Aung; Nandar Hlaing; Tun Lin (Yayasan Adra Karima Hubbi, 2025)
Virtual reality (VR) technology has shown great potential in various sectors, including the agricultural sector which requires practical training. This study aims to evaluate the effectiveness of VR technology in improving the skills of farmers in Switzerland through agricultural training. This study uses a quasi-experimental method by comparing the group that uses VR training and the control group that uses conventional methods. The results showed that participants who took part in VR-based training had significant skill improvements and higher levels of satisfaction compared to traditional methods. Despite the challenges of early adaptation to VR technology, participants generally found the learning experience to be more interactive and effective. The conclusion of this study states that VR can be an effective tool in developing farmers’ technical skills in a safer, more flexible, and interactive way. More research is needed to explore the long-term use of VR in agricultural training.